The gathering storm - Jordan, Robert, 1948-2007 (Jordan, Robert, 1948-2007. Wheel of time, 2009)
Rand al'Thor, the Dragon Reborn, struggles to unite a fractured network of kingdoms and alliances in preparation for the Last Battle. Meanwhile, Egwene al'Vere, the Amyrlin Seat of the rebel Aes Sedai, is being held captive by the White Tower. Knowing the Seanchan attack is imminent, she fights to hold the Aes Sedai together in an epic contest that will prove the mettle of her followers and will decide the future of the White Tower---and possibly the world itself. The first of three novels that will make up "A Memory of Light" and mark the conclusion of the Wheel of Time.